AB0476 SPECIAL ASPECTS OF GLUCOCORTICOID THERAPY IN PATIENTS WHO TREATED WITH ANTI-B-CELL AND ANTI-BLYS THERAPY. (June 2019) - Mesnyankina, Anna; Solovyev, Sergey; Aseeva, Elena; Nasonov, Evgeny
Abstract : Background: The basis of treatment of SLE are glucocorticoids (GCs), which since their introduction into clinical practice, have led to increased survival and reduced early mortality of SLE patients. However, the need to use high doses of GCs, as well as long-term use of medium doses to maintain disease remission, leads to the development of serious adverse reactions. This leads to an increase in the risk of irreversible organ damage. In this regard, it is important to search for ways to prevent the use of high doses of GCs, minimizing the dose of GCs. Objectives: To assess special aspects and dynamics of oral glucocorticoid (GC) therapy in SLE patients treated with anti-B-cell and anti-BlyS therapy. Methods: The study included 64 SLE pts (5М/58F), divided into 3 groups: Group I - 47 patients (SLEDAI2K 16[11;20] scores), receiving rituximab (RTX) i/v infusions by drop at 500 - 2000 mg dose-range. Group II included 10 patients (SLEDAI2K 10[8;11] scores) treated with Belimumab (BLM) at 10 mg/kg once a month. The remaining 7 patients from Group III (SLEDAI2K 10[9;16] scores) were administered a combination of RTX and BLM. They started treatment with RTX 500 (2 patients) or 1000 mg (5 patients) infusions, and 3 months later BLM at standard scheme of 10 mg/kg once a month was initiated for 8 months. SLICC damage index (DI) was documented at baseline - before initiation of RTX and BLM - in 26 out of 64 patients (40%) with SLICC DI score > 1 (1 - 5 scores); 20 patients out of them were administered RTX. Results: 47 patients on RTX therapy received different oral GCs doses: high GCs doses (Me 40[30;50]mg/day) were documented in 11 (24%) patients, moderate doses (Me 13[10;20]mg/day) – in 29 (61%) patients, and low doses (Me 5[5;7, 5]mg/day) - in 7 (15%) patients. Patients on BLM and combination therapy were administered GCs at doses ≤ 20 mg (Me 15[5;20]mg/day and Me 8, 75[5;15] mg/day, respectively) During first 3 month of treatment GCs doses in all 3 Groups remained unmodified. By Mo 6 25% reduction in oral GCs doses was documented in: patients on RTX - 20[15;20]mg/day, 10[8, 75;10]mg/day, 5[5;5] mg/day (respectively, in the groups with initially high, moderate and low GCs doses); BLM 10[7, 5;10] mg/day, combination therapy 8, 75[5;15] mg/day. By Mo 12 Me GCs dose in all 3 Groups did not exceed 10 mg/day. In view of SLE exacerbations in patients from Group I (RTX) additional RTX infusions at Mo 6, 9 and 12 were administered in 8 (20%) patients. Figure 1 presents the dynamics of oral GCs doses in patients from Group I (RTX), who were divided in 3 subgroups based on baseline (high, moderate or low) GCs dose, and also dynamics of GCs dose in patients from Groups II (BLM) and III (RTX+BLM). Increase in SLICC score by Mo 12 of follow up was documented in patients on RTX therapy with baseline pre-existing organ damage (5 patients). There was no increase in SLICC scores in BLM and RTX+BLM treatment groups. Conclusion: Combination therapy results in achieving rapid control of SLE activity thanks to RTX effects, and the combination with BLM allows significantly prolongs this result, minimizing the risk of exacerbation. And a very specific gain from combination RTX+BLM therapy is a chance to manage patients on moderate-to-low oral GCs doses, therefore, reducing the risk of irreversible organ damage. Increasing organ damage score in RTX Group is most likely associated with intake of higher GCs doses. Disclosure of Interests: Anna Mesnyankina: None declared, Sergey Solovyev: None declared, Elena Aseeva: None declared, Evgeny Nasonov Speakers bureau: Pfizer, Inc., MSD, Novartis, AbbVie Inc., Celgen Corporation, Biocad, Janssen, UCB, Inc.